2018
DOI: 10.1016/j.compstruct.2018.06.091
|View full text |Cite
|
Sign up to set email alerts
|

A review of analytical models to describe pull-out behavior – Fiber/matrix adhesion

Abstract: Micromechanical tests are reliable tools to study the failure mechanisms in composites reinforced with continuous fibers. This paper presents an overview of various analytical models developed to study the pullout (push-back) behavior of a fiber embedded in a matrix block to characterize the fiber/matrix interfacial adhesion. Two approaches can be distinguished: one based on a maximum stress criterion (shear lag) and the other based on fracture mechanics. This article gives an overview of the analytical models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 163 publications
1
25
0
Order By: Relevance
“…It is also worth emphasising the dense transverse multi‐cracking that occurs in the matrix that penetrated into the yarn, illustrated by the zoom made in the transversal slice on Figure 13b. This damage pattern is also similar to those observed in other brittle matrix composite 4, 40 and is the sign of a great interfacial bond and a good penetration of the matrix inside the yarn. The spacing is here smaller than the one observed in BF + NAG3 sample and equals to about 50 μm.…”
Section: Interfacial Damage Of Various Single Yarns Embedded In Mortasupporting
confidence: 85%
See 2 more Smart Citations
“…It is also worth emphasising the dense transverse multi‐cracking that occurs in the matrix that penetrated into the yarn, illustrated by the zoom made in the transversal slice on Figure 13b. This damage pattern is also similar to those observed in other brittle matrix composite 4, 40 and is the sign of a great interfacial bond and a good penetration of the matrix inside the yarn. The spacing is here smaller than the one observed in BF + NAG3 sample and equals to about 50 μm.…”
Section: Interfacial Damage Of Various Single Yarns Embedded In Mortasupporting
confidence: 85%
“…This methodology allows for the determination of respective interfacial parameters, usually fitting maximal pull-out force and residual frictional force, whenever non null. A recent review of pull-out tests is provided by Teklal et al [18] . With multi-fibre yarns, impregnation by the cementitious matrix has been evidenced, from scanning electron microscopy (SEM) observations and mechanical tests, to constitute a key parameter [19] [20] influencing pull-out properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous experimental tests have been proposed in literature to quantify strength and mechanical behavior depending on the material used and fiber geometry at different scale. Reviews of these investigations can be found in [6,7].…”
Section: Determination Of Interfacial Mechanical Properties Using Mesmentioning
confidence: 99%
“…Teklal et al. 26 presented an overview of the analytical models reported in the literature to measure the shear strength and critical fracture energy at the interface, the parameters influencing these properties, the geometry of the model, embedded length of the fiber, fiber diameter and loading conditions, including, manufacturing route and the resulting defects.…”
Section: Introductionmentioning
confidence: 99%